1963
DOI: 10.1099/00221287-30-1-59
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Replication of the Trachoma Agent in Cell Cultures, as shown by Electron Microscopy

Abstract: SUMMARYPropagation of the trachoma agent in human cell cultures has made possible the observation by electron microscopy of sequential stages in the replication of the micro-organism. Scattered reticular foci with incomplete limiting membranes were present in the cytoplasm of HeLa cells 12 hr. after exposure to the infectious agent in high multiplicity. After 24 hr. the foci had coalesced to give a single reticular mass. Within it there appeared large and discrete developmental forms from which, by progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1963
1963
1986
1986

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Thin sections of the infected host cells contained many forms apparently fixed in the act of binary fission (5-7, 44, 47, 55-57, 66-68, 77, 78, 100). In addition to these dividing forms, many workers also saw structureless matrices in the cytoplasm of host cells infected with the agents of meningopneumonitis and trachoma in which new agent cells were ap parently being organized by some virus-like reproductive process (7,23,58,77,79,100,115) . However, more recent work (6,56) demonstrated that these matrices were artifacts resulting from the disruption of the fragile large de velopmental forms during fixation and embedding of the infected cell for thin-sectioning.…”
Section: Developmental Cyclementioning
confidence: 97%
“…Thin sections of the infected host cells contained many forms apparently fixed in the act of binary fission (5-7, 44, 47, 55-57, 66-68, 77, 78, 100). In addition to these dividing forms, many workers also saw structureless matrices in the cytoplasm of host cells infected with the agents of meningopneumonitis and trachoma in which new agent cells were ap parently being organized by some virus-like reproductive process (7,23,58,77,79,100,115) . However, more recent work (6,56) demonstrated that these matrices were artifacts resulting from the disruption of the fragile large de velopmental forms during fixation and embedding of the infected cell for thin-sectioning.…”
Section: Developmental Cyclementioning
confidence: 97%
“…2 ,~ elementary bodies when multiplying by binary fission. On the other hand, electron micrographs of thin sections of cells infected with high multiplicities of psittacosis organisms (Tajima, Nomura & Kubota, 1957) and trachoma organisms (Armstrong et al 1963) indicate that an early stage of development is the formation of comparatively large bodies or plaques. In the first 24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…D, for the Chlamydia suspension at different teuiperatures was KT calculated from formula D = j for spherical particles in Brownian motion {Einstein, ftTTTja 1906), where « = Boltzmann's constant (1-38 x lO-i"); T = the absolute temperature; II = the viscosity of the suspending fluid (poise) and a = the radius of the particles (cm). The value of a was taken as 0-151 x 10~^ cm, from the electron microscopy measurements of trachoma elementary bodies by Armstrong, Valentine and Fildes (1963), who suggested that tliese Chlamydia elementary bodies were truly spherical structures,…”
Section: Diffusion Constant Of Susperu^ionmentioning
confidence: 99%